Social networks and vaccination decisions - Neel Rao; Markus M. Möbius; Tanya Rosenblat (Federal Reserve Bank of Boston, 2007)
We combine information on social networks with medical records and survey data in order to examine how friends affect one's decision to get vaccinated against the flu. The random assignment of undergraduates to residential halls at a large private university allows us to estimate how peer effects influence health beliefs and vaccination choices. Our results indicate that social exposure to medical information raises people's perceptions of the benefits of immunization. The average student's belief about the vaccine's health value increases by 5.00 when an additional 10 percent of her friends are assigned to residences that host inoculation clinics. Among students with no recent flu experience, a 10 percent rise in the number of friends living in residences with clinics raises cumulative valuations of the vaccine by 10.92, with 85 percent of this increase attributable to heightened perceptions about the medical benefits of immunization. We also find evidence of positive peer effects on individuals' vaccination decisions. A student becomes up to 8.3 percentage points more likely to get immunized if an additional 10 percent of her friends receive flu shots. Furthermore, the excess clustering of friends at inoculation clinics suggests that students coordinate their vaccination decisions with their friends.
Keywords: I18; C93; Z13; 330; social networks; peer effects; economic experiments; random assignment; vaccination; Soziales Netzwerk; Soziale Gruppe; Impfung; USA